2016
DOI: 10.1016/j.jenvman.2016.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal persistence of faecal indicator organisms in soil following dairy slurry application to land by surface broadcasting and shallow injection

Abstract: Dairy farming generates large volumes of liquid manure (slurry), which is ultimately recycled to agricultural land as a valuable source of plant nutrients. Different methods of slurry application to land exist; some spread the slurry to the sward surface whereas others deliver the slurry under the sward and into the soil, thus helping to reduce greenhouse gas (GHG) emissions from agriculture. The aim of this study was to investigate the impact of two slurry application methods (surface broadcast versus shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, less E. coli were transferred to growing spinach plants in the spring compared to the fall season due to the lower E. coli populations present in the soil. Similarly, E. coli and enterococci populations in grassland plots amended with dairy manure slurry had greater half lives in autumn and summer seasons compared to a spring season (39). Other researchers have shown that survival durations of E. coli O157:H7 differ in different spring seasons evaluated at the same site (40).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, less E. coli were transferred to growing spinach plants in the spring compared to the fall season due to the lower E. coli populations present in the soil. Similarly, E. coli and enterococci populations in grassland plots amended with dairy manure slurry had greater half lives in autumn and summer seasons compared to a spring season (39). Other researchers have shown that survival durations of E. coli O157:H7 differ in different spring seasons evaluated at the same site (40).…”
Section: Discussionmentioning
confidence: 87%
“…7), low gEc and attO157 inocula in HM-amended soils were the only amendment/inoculum treatment where no surfaceamended profiles survived for greater durations than tilled-in profiles. Other work has shown that E. coli survival durations were greater in grassland soils injected with dairy manure slurry compared to soils where dairy manure was surface broadcast (39). Similarly, E. coli O157:H7 survival durations were also greater at a depth of 15 cm in swine and dairy manure-amended soils than in surface-amended soils (40).…”
Section: Discussionmentioning
confidence: 87%
“…The heterogeneous nature of the above five categorized materials and their diverse treatment conditions like moisture level, seasonality, application dose, and condition were also considered to cover the wide range of data set. Data were obtained from tables or log-linear regression equations where available (Himathongkham et al, 1999;Oliver et al, 2006;Lang and Smith, 2007;Martinez et al, 2013;Hodgson et al, 2016;Roberts et al, 2016); otherwise, data were extracted from digitized figures to derive log-linear regression equation by plotting Log 10 CFU g −1 dw vs. Time (days) (Avery et al, 2004(Avery et al, , 2005Oliver et al, 2010;Schwarz et al, 2014;Biswas et al, 2018;Ellis et al, 2018). The die-off pattern of pathogens can be described by the first-order kinetics Equation 1, which upon integration gives the linear Equation 2 (Mubiru et al, 2000;Martinez et al, 2013).…”
Section: Empirical Data On E Coli Concentration and Decay Ratementioning
confidence: 99%
“…In scenario 3, E. coli survival pattern in dairy slurry application associated soil was assessed based on the empirical data (Tables 1, 2) from five reference studies as shown in Figure 1C. In this case, the C 20 , log 10 CFU ml −1 concentrations were 0.12, 1.47, 1.12, 1.23, 0.90, and 0.74 compared to the initial value of 6.43 from Himathongkham et al (1999), Avery et al (2005), Oliver et al (2006), Hodgson et al (2016), and Biswas et al (2018). The C 40 concentration ranged from 0.002 to 0.34 log 10 CFU ml −1 for all five reference studies.…”
Section: E Coli Survival Pattern Across Six Scenariosmentioning
confidence: 99%
“…For example, Samarajeewa et al (2012) found E. coli and C. perfringens in shallow groundwater and tile drainage water samples within 3-10 days of applying swine manure to loamy soil in southern Ontario. The practice of injecting manure into the soil as a mean to reduce greenhouse gas emissions and nutrient losses may increase survival times of pathogens after manure application (Hodgson et al 2016).…”
Section: Agronomic Aspects: Nutrient Contents and Transformationsmentioning
confidence: 99%